How Can Good Guanxi Be Cultivated? An Exploratory Study Into Indonesian and Malaysian Small and Medium Enterprises (SMEs) - Ng, Su Yin (2005)
There have been numerous studies into the idea and concept of guanxi in China. Given the notion that guanxi is the power to get things done, or at least the ‘lubricant’ to smoothen business operations, it is not surprising that guanxi is a favourite subject amongst businesspeople, especially the people who intends to do business in China, or those who are planning to do business with the Chinese community. Whilst there have been practical evidence of guanxi in the business conduct of Chinese outside China, as can be observed in the business practices in out everyday lives, there was little, if any, research conducted with the attempt to understand how the Chinese community outside of China build up relationships and good guanxi in order to support their businesses. The study was conducted using both questionnaire survey and the qualitative method if indepth interviews. The questionnaire survey was shaped to find out which element of guanxi play the most important role in doing business, whilst the second and major part of the paper endeavours to seek an understanding into the manner and means with which small and medium- sized enterprises (SMEs) in Indonesia and Malaysia build up relationship and cultivate good guanxi in doing business using the relationship cultivation strategies adopted from the theory of public relations. The results show that guanxi does play a role in doing business, with relationship (ganqing)being the most dominant determining factor, and that the relationship cultivation strategies perpetuated by the theory of public relations are feasible in helping to build up good guanxi, although the effect of all the six strategies are different.